A relação entre seres humanos e animais da perspectiva do Budismo Moderno da Nova Tradição Kadampa - Silva, Laís Monteiro Bartolozzi (Universidade Federal de São Carlos, 2022)
This course conclusion research investigates a modern Buddhist theological narrative based on the relationship between human and non-human beings, aiming to explore the depth of this relationship, as expressed philosophically, materially and ontologically, in practical actions observed in the field research carried out at the Templo Budista: Centro de Meditação Kadampa Brasil. This paper seeks an anthropological reflection on the contemporary Buddhist understanding of the importance of all living beings. The developed Buddhist concepts have the objective of a better understanding of this religion, for, consequently, to understand how these concepts can help us to think about our relationship with the animals in the contemporaneity.

Este trabajo de conclusión del curso investiga la narrativa teológica budista moderna. basado en la relación entre seres humanos y no humanos, con el objetivo de explorar la profundidad de esta relación, tal como se expresa filosófica, material y ontológicamente, en acciones prácticas observadas en la investigación de campo. desarrollado en el Templo Budista: Centro de Meditación Kadampa Brasil. Éste El trabajo busca una reflexión antropológica sobre la comprensión budista. contemporáneo sobre la importancia de todos los seres vivos. Conceptos budistas desarrollados tienen como objetivo una mejor comprensión de esta religión, para, en consecuencia, entendemos cómo estos conceptos pueden ayudarnos a Pensemos en nuestra relación con los animales en la época contemporánea.
The relationship between humans and animals from the perspective of Modern Buddhism of the New Kadampa Tradition
La relación entre humanos y animales desde la perspectiva del Budismo Moderno de la Nueva Tradición Kadampa
Keywords: Relação entre seres humanos e não humanos; Budismo; Sofrimento; Compaixão; Especismo; Transformação; Relationship between human and non-human beings; Buddism; Suffering; Compassion; Speciesism; Transformation; Relación entre seres humanos y no-humanos; Budismo; Sufrimiento; Compasión; Especismo; Transformación; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA URBANA